Réponses

Meilleure réponse !
  • Utilisateur Brainly
2013-03-30T17:49:54+01:00

A= (3x +1)(x-5)

= 3x * x + 3x * -5 + 1 *x + 1 *-5

= 3x² -15x +x -5

= 3x² - 14x -5

 

Pour x = 0:

3*0² -14 *0 -5 = -5

 

Pour x = 1:

3 * 1² - 14 *1 -5

= 3 -14 -5 = -20

 

Pour x = -4:

3*-4² - 14 * -4 -5

= 3* -16 + 56 -5

= -48 + 56 -5 = ...

 

Je te laisse faire la suite

C'est le meme principe pour x =5/3

 

2013-03-30T17:51:53+01:00
A=3x^2-15x+x-5=3x^2-14x-5
Si x=0 A=1*(-5)=-5
Si x=1 A=3-14-5=-16
Si x=-4 A=(-12+1)(-4+5)=-11*1=-11
Si x=5/3 A=(5+1)(5/3-15/3)=6*(-10/3)=-20